High-Performance Soy Protein Isolate-Based Film Synergistically Enhanced by Waterborne Epoxy and Mussel-Inspired Poly(dopamine)-Decorated Silk Fiber - Pang, Huiwen (Polymers (Basel), 2019)
It remains a great challenge to fabricate bio-based soy protein isolate (SPI) composite film with both favorable water resistance and excellent mechanical performance. In this study, waterborne epoxy emulsions (WEU), which are low-cost epoxy crosslinkers, together with mussel-inspired dopamine-decorated silk fiber (PSF), were used to synergistically improve the water resistance and mechanical properties of SPI-based film. A stable crosslinking network was generated in SPI-based films via multiple physical and chemical combinations of WEU, PSF, and soy protein matrixes, and was confirmed by attenuated total reflectance-Fourier transform infrared (ATR-FTIR) spectroscopy, X-ray diffraction (XRD), and solid state (13)C nuclear magnetic resonance ((13)C NMR). As expected, remarkable improvement in both water resistance and Young’s modulus (up to 370%) was simultaneously achieved in SPI-based film. The fabricated SPI-based film also exhibited favorable thermostability. This study could provide a simple and environmentally friendly approach to fabricate high-performance SPI-based film composites in food packaging, food preservation, and additive carrier fields.